Influence of the production systems of forested organic coffee on the diversity of the in epigeic invertebrate fauna - Guimarães, Nathalia de França; Gallo, Anderson de Souza; Souza, Maicon Douglas Bispo de; Agostinho, Patricia Rochefeler; Gomes, Michele da Silva; Silva, Rogério Ferreira da (Coffee Science - ISSN 1984-3909, 2015)
The work had as objective to evaluate the influence of systems of production of woody organic coffee on the diversity of the epigeic invertebrate fauna. The study it was lead in a sandy texture Ultisol. The adopted design was the randomized blocks, in subdivided parcels, with five repetitions. The main parcels had been the handling systems: organic coffee (CO), joined organic coffee with four vegetal species (CO4), joined organic coffee with nine vegetal species (CO9), joined organic coffee with five vegetal species (CO5), joined organic coffee with Musa spp. (CB) and in area of native vegetation (VN). Subparcels had been the times of evaluation (october/2012 and july/2013). In each system they had been installed five trap of fall “pitfall” for capture of the epigeic invertebrate fauna. Moreover, the amount of burlap (t ha-1), next was evaluated to the traps. In all the systems had great dominance of Collembola. The density and the wealth of epigean macroinvertebrates had been influenced by the systems of handling of the ground and by the times of sampling.